ANALYSIS OF LOCAL WISDOM IN THE FIELD OF BIOTECHNOLOGY IN MAKING CASSAVA TAPAI (TAPAI SINGKONG) IN PETAK TALAO MUNDAM, NAGARI KATAPIANG - Suci Rafifah (SEMESTA: Journal of Science Education and Teaching, 2022)
In order to examine local knowledge from the fermentation process used to make tapai cassava, this observation will link it to ethnoscience. This observation was made in the areas of Padang Pariaman, Petak Talao Mundam, Nagari Katapiang, and Jl. Minang Kabau International Airport. With the sources Mr. Sisul and Mrs. Maryam. In making cassava tapai it has several stages, starting from selecting good cassava, peeling the cassava skin, cutting, washing, boiling, cooling, giving yeast, the fermentation process to become a cassava tapai. The fermentation process in making cassava tapai gives changes in color, aroma typical tapai, soft texture, and sour taste. Tapai cassava has many benefits such as; to expedite the menstrual process, get rid of acne, medicine for wounds for diabetics, warm the body, remove black spots, and etc.